2018
DOI: 10.1016/j.jtcvs.2018.01.088
|View full text |Cite
|
Sign up to set email alerts
|

Training cardiothoracic surgeons of the future: The UK experience

Abstract: Live animal operating as a component of targeted cardiothoracic surgery skill training courses significantly improves technical skills, builds confidence of surgical trainers in resident physicians' practice, and should be supported by the surgery community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In Semester 2, most students agreed that ProgSD had helped them prepare for the S2 courses they were taking as they were able to apply the skills they gained through the Bootcamp in those Semester 2 courses. Similar observations were made in the literature that Bootcamps help improve skills and self-confidence in applying knowledge and skills important to students' majors (Alavi et al, 2020, June;Fronza et al, 2020;Kenny et al, 2018;Lerner et al, 2018). That increase in confidence can last for at least six months (Selden et al, 2013), thus supporting the idea that the ProgSD Bootcamp had a positive effect on student knowledge and skills retention.…”
Section: Improving Students' Practical Skills Through Bootcamp Coursessupporting
confidence: 82%
“…In Semester 2, most students agreed that ProgSD had helped them prepare for the S2 courses they were taking as they were able to apply the skills they gained through the Bootcamp in those Semester 2 courses. Similar observations were made in the literature that Bootcamps help improve skills and self-confidence in applying knowledge and skills important to students' majors (Alavi et al, 2020, June;Fronza et al, 2020;Kenny et al, 2018;Lerner et al, 2018). That increase in confidence can last for at least six months (Selden et al, 2013), thus supporting the idea that the ProgSD Bootcamp had a positive effect on student knowledge and skills retention.…”
Section: Improving Students' Practical Skills Through Bootcamp Coursessupporting
confidence: 82%
“…All studies presented have demonstrated that simulation-based training in cardiothoracic surgical procedures enhances the learning experience and improve trainee performance to some degree, allowing for repetitive training until the acquisition of competence (22,(46)(47)(48). Nonetheless, the focus of simulation is not only the advanced technology and devices that make them life-like but the content of the educational curricula and the availability of trained surgical educators that make it possible to measure skills performance (49).…”
Section: P a G E | 11mentioning
confidence: 99%
“…Kenny and colleagues 1 provide a good first step in the systematic evaluation of simulation and live operating boot camp experiences. 1 Others have demonstrated similar results in improving the confidence of trainees, 2,3 and it is well known that confidence is a key trait of a successful surgeon. Long-term sustainability and applicability of knowledge gained in boot camps (as a significant improvement relative to others who have trained in the traditional manner) were not clearly demonstrated.…”
mentioning
confidence: 90%